Promoting the Chinese martial arts internationally: Is it 'Kung Fu' or 'Wushu'?. (May 2023) - Han, Qing-song; Theeboom, Marc; Zhu, Dong; Derom, Inge
The term 'Kung Fu' is used internationally more often than its official name 'Wushu' to depict the Chinese martial arts. Yet the latter term has been promoted by the Chinese government for nearly 50 years and also used by the International Wushu Federation (IWUF) during the past three decades. This paper examines the distinction in the meaning between both terms through Stuart Hall's Representation Theory, based on 20 in-depth interviews with international expert witnesses. Findings suggest that the term 'Kung Fu' is mostly associated with traditional Chinese martial arts, Kung Fu cinema, Oriental imagination, and fighting practicability. For expert witnesses, Kung Fu represents an identity of traditional Chinese martial arts and a way to experience 'Chineseness'. By contrast, although the IWUF has made efforts to package Wushu as the term representing Chinese martial arts, 'Wushu' is regarded as a competitive sport, shaped significantly by IWUF's Olympic ambition. Also, three key aspects regarding the representation of the Chinese martial arts in relation to both terms are discussed.